Antimicrobial and Defense Proteins in Chronic Rhinosinusitis with Nasal Polyps - Rudolfs Janis Viksne; Gunta Sumeraga; Mara Pilmane (Medicina, 2023)
Background and Objectives: Chronic rhinosinusitis with nasal polyps (CRSwNP) presently remains a difficult disease to manage. Antimicrobial and defense proteins are important factors that could help characterize the role of microorganisms in CRSwNP pathogenesis, as the concept of microbial dysbiosis in CRS is still being considered. Our aim is to investigate the complex appearance, relative distribution and interlinks of human β defensin 2 (HBD-2), human β defensin 3 (HBD-3), human β defensin 4 (HBD-4), and cathelicidin LL 37 (LL 37) in chronic rhinosinusitis with nasal polyps (CRSwNP)-affected human nasal mucosa. Materials and Methods: The study group consisted of 48 samples from patients with CRSwNP. Samples were collected during functional endoscopic sinus surgery. The control group consisted of 17 normal healthy nasal mucosa samples gathered during routine septoplasty. β-defensin-2, β-defensin-3, β-defensin-4 and cathelicidin LL 37 in tissue were detected via immunohistochemical analysis. Results: HBD-2, HBD-3 and LL 37 were significantly decreased in epithelial cells in both primary and recurrent nasal polyp samples (p < 0.001) in comparison to control samples. HBD-2 was decreased in the subepithelial connective tissue of primary nasal polyp samples when compared to both recurrent polyp (p = 0.050) and control (p = 0.033) samples. In subepithelial connective tissue, significantly more HBD-3-positive structures were observed in primary nasal polyp samples (p = 0.049) than in control samples. In primary polyp samples, moderate correlations between connective tissue HBD-3 and connective (R = 0.584, p = 0.001) and epithelial tissue LL 37 (R = 0.556, p = 0.002) were observed. Conclusions: Decreased HBD-2, HBD-3 and LL 37 concentrations in the epithelium suggest a dysfunction of the epithelial barrier in patients with nasal polyps. Decreased subepithelial connective tissue HBD-2 suggests different responses to nasal microbiota in patients with primary nasal polyps compared to recurrent nasal polyps. Increased HBD-3 in subepithelial connective tissue suggests a possible role of this antimicrobial peptide in the pathogenesis of primary nasal polyps.